2010
DOI: 10.1007/s11240-010-9697-5
|View full text |Cite
|
Sign up to set email alerts
|

Simulating in ovulo osmotic potentials and O2 tensions normalize growth and pigmentation of immature cotton embryos

Abstract: Oxygen tensions and osmotic potentials are important physiological factors of plant growth and development. To optimize these variables for cotton (Gossypium hirsutum L.) embryo culture, we quantified dissolved O 2 (dO 2 ) tensions, osmotic potentials, and pH at several locations in cotton ovules during embryony. Clark O 2 microelectrodes were micromanipulated into intact ovules at an angle lateral to the developing embryo, and dO 2 tensions were determined in integuments, nucelli and embryos. Ovular osmotic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2010
2010
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 30 publications
(46 reference statements)
1
8
1
Order By: Relevance
“…Even these plastids have a well developed thylakoid system, even if not so well developed as in the other two endosperm compartments. ROLLETSCHEK et al (2003) and LIDDIARD and CARMAN (2010) suggested that O2 production by photosynthetic activity in the seed could be necessary to provide O2 to the developing embryo, particularly if the seed coat acts as a barrier against the diffusion of this gas. Moreover the amount of functional chloroplasts in the seed of Eruca suggests that the photosynthetic product could be a relevant part of the carbohydrates necessary for the anabolic activity in the developing embryo.…”
Section: Discussionmentioning
confidence: 99%
“…Even these plastids have a well developed thylakoid system, even if not so well developed as in the other two endosperm compartments. ROLLETSCHEK et al (2003) and LIDDIARD and CARMAN (2010) suggested that O2 production by photosynthetic activity in the seed could be necessary to provide O2 to the developing embryo, particularly if the seed coat acts as a barrier against the diffusion of this gas. Moreover the amount of functional chloroplasts in the seed of Eruca suggests that the photosynthetic product could be a relevant part of the carbohydrates necessary for the anabolic activity in the developing embryo.…”
Section: Discussionmentioning
confidence: 99%
“…Low O 2 tensions next to cultured embryos were established and maintained as in Liddiard and Carman (2010). In brief, this included the use of an autoclavable polycarbonate plastic culture chamber with gas inlet and outlet ports and an E-444 O 2 sensor (Remming Bio Instruments Co., Redfield, NY) that was attached to a CR-10 data logger (Campbell Scientific, Inc., Logan, UT).…”
Section: Methodsmentioning
confidence: 99%
“…The latter approach is becoming increasingly feasible because of advancements in chemical and biophysical measurement instrumentation of small samples (Murray 1963;Carman 1995;Otegui et al 2002;Carman et al 2005;Fuller et al 2009;Liddiard and Carman 2010). For the present study, we hypothesized that the routine regeneration of isolated cotton proembryos by direct embryogenesis in vitro could be accomplished by simulating the nutritional and hormonal requirements of embryony in situ.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations